Thematic-Based Text Structure Analysis as a Function of Text Memorization: Surah Yasin - Sidek, Hanison Mohd; Saleh, Muhammad Hafiz; Husin, Hayati (Univ Putra Malaysia Press, 2024)
Indexed by WOS/Scopus/ERA